1984
DOI: 10.1099/00207713-34-4-451
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus azotofixans sp. nov., a Nitrogen-Fixing Species from Brazilian Soils and Grass Roots

Abstract: A new species, Bacillus azotojixans, is described. This taxon is based upon 16 soil and root-associated strains that exhibit acetylene-reducing ability and nitrogen-fixing Bacillus sp. strain Hino. B . azotojixans is phenotypically similar to Bacillus polymyxa and Bacillus macerans. However, 13 tests (nitrate reduction; production of acid and gas from xylose, arabinose, lactose, ribose, and glycerol; resistance to lysozyme; liquefaction of gelatin; starch hydrolysis; decomposition of casein and pectin; product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
114
0
5

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 19 publications
3
114
0
5
Order By: Relevance
“…The GjC contents of DNA of isolates KK19 T (54 mol %) and KM8 (50 mol %) were higher than that of P. polymyxa (43-46 mol %) (Shida et al, 1997). Nitrogen fixation was not inhibited by 0n5% (w\v) NaNO $ in any of the isolates, whereas Seldin et al (1984) showed that nitrate inhibited nitrogen fixation in P. polymyxa and P. macerans. The seven isolates differed from P. polymyxa by negative reactions for ribose and rhamnose fermentation, nitrate reduction, gelatin liquefaction and Voges-Proskauer, and by a positive reaction for melezitose.…”
Section: Chemotaxonomic and Physiological Propertiesmentioning
confidence: 84%
“…The GjC contents of DNA of isolates KK19 T (54 mol %) and KM8 (50 mol %) were higher than that of P. polymyxa (43-46 mol %) (Shida et al, 1997). Nitrogen fixation was not inhibited by 0n5% (w\v) NaNO $ in any of the isolates, whereas Seldin et al (1984) showed that nitrate inhibited nitrogen fixation in P. polymyxa and P. macerans. The seven isolates differed from P. polymyxa by negative reactions for ribose and rhamnose fermentation, nitrate reduction, gelatin liquefaction and Voges-Proskauer, and by a positive reaction for melezitose.…”
Section: Chemotaxonomic and Physiological Propertiesmentioning
confidence: 84%
“…Johanna Döbereiner also made an initial contribution to the study of the nitrogen-fixing bacterium Paenebacillus azotofixans (formerly Bacillus azotofixans) (Seldin et al 1984 . A "rhizosphere effect" promoted by the wheat rhizosphere was also demonstrated (Rosado et al 1996).…”
Section: Paenebacillus Azotofixansmentioning
confidence: 99%
“…Members of both genera have physiologically diverse characteristics and some species are known to secrete a variety of extracellular enzymes, such as polysaccharide-hydrolysing enzymes, or to produce polysaccharides (Claus & Berkeley, 1986;Priest, 1977;Chung et al, 2000; Seo et al, 1999). Species of the genus Paenibacillus have been isolated from a wide range of sources including soil, water, plant rhizospheres, plant materials, food, fodder, faeces and diseased insect larvae (Alexander & Priest, 1989;Kanzawa et al, 1995;Montefusco et al, 1993;Nakamura, 1984Nakamura, , 1987Seldin et al, 1984;Shida et al, 1997;Yoon et al, 1998).The Woopo wetland (35 u 339 N, 128 u 259 E), located to the east of the Nakdong river, Republic of Korea, was created about 140 million years ago, is surrounded by low-level mountains and has a levee that was built to protect agricultural areas. The wetland types are classified as 'O', permanent freshwater lakes over 8 ha, including large oxbow lakes; and 'Tp', permanent freshwater marshes, pools or ponds below 8 ha, marshes and swamps on inorganic soils with emergent vegetation and that are waterlogged for most of the growing season (http://www.…”
mentioning
confidence: 99%